Comparative Analysis of the Yakut-Mongolian Parallels (the Case of the Horse Coat Color) - Malysheva, Ninel; Bozhedonova, Alla; Starostina, Yana (Journal of History Culture and Art Research, 2018)
The purpose of this article is to identify the phonostructural and lexical-semantic features of the Yakut-Mongolian lexical parallels, denoting the names of the horse coat color. It is known that the horse is a sacred animal in the Yakut and Mongolian culture and therefore the terminology of horse breeding is very developed and rich in both languages. In the furtherance of this goal, we used several methods of research; the main ones are component and distributive analyses. We used the component analysis to reveal the lexical-semantic feature of the parallels. The lexemes were divided into three groups: a) the stability of the lexical meaning of the word; b) a partial coincidence of the lexical meaning of the word; c) a noticeable change in the lexical meaning of the word. With the help of distributive analysis, we showed the phonostructural feature of the adjectives’ names, denoting the name of the horse coat colors, and also revealed ethnocultural differences and similarities. As a result of the study, 13 Yakut-Mongolian parallels were found. As is known, there are about 200 kinds of horse coat colors, and to distinguish all of them, different nations use their complex adjectives. Therefore, the Yakut-Mongolian parallels are divided into 2 categories: one-component (9 items) and two-component (4 items). When analyzing the structural type of one-component lexical parallels, it was revealed that 4 out of 9 parallels were subjected to a structural change. Of the 5 parallels with the absolute coincidence of the structural types there are three Yakut stems: "sālïr ", "būlur", "kürӓŋ ", in all probability, they are late borrowings from the Mongolian language. Component analysis has shown that preservation of the stability of lexical meanings is noted in 31% (4) parallels, a slight lexical change occurred in 39% (5) parallels, notable lexical changes - in 31% (4) parallels.